Visual acuity and correctable visual impairment among Norwegian 65-year olds - Sundling, Vibeke (Scandinavian Journal of Optometry and Visual Science, 2011)
Prevalence of ocular disease and visual impairment increases with increased age. Population studies have shown that uncorrected refractive error is the main cause of visual impairment in the general population. The aim of this study was to examine visual acuity (VA) and the prevalence of correctable visual impairment among Norwegian 65-year-olds. The study had a crosssectional design. A random sample born in 1943 (n = 300) was invited to participate. The participants underwent a full eye examination including: patient history, habitual visual acuity (HVA), refraction, best corrected visual acuity (BCVA) and examination of ocular health. The study was approved by the Regional Committee for Medical Research Ethics and reported to the Norwegian Social Science Data Services. Data was analyzed by Fisher’s exact test, χ2-test, student t-test and logistic regression, p < 0.05 was considered statistically significant. Relative risk (RR) and odds ratio (OR) were calculated for correctable visual impairment. In all 129 subjects (43%) participated in the study. Three were excluded from the analysis due to missing data. The analysis included 126 subjects, 67 males and 59 females. None of the participants had permanent visual impairment. Mean (±SD) BCVA was logMAR -0.06 (±0.10) (Snellen decimal 1.2). Six subjects (5%) had correctable visual impairment, HVA logMAR > 0.3 (Snellen < 0.5) in the better eye, which improved with best correction to logMAR ≤ 0.3 (Snellen > 0.5). Eight subjects (6%) had clinically relevant undercorrected refractive error, i.e. an undercorrection in refractive error which when corrected produced an improvement in VA of 10 letters (2 lines on the logMAR chart) or more after refraction, when HVA was logMAR < 0.2 (Snellen 0.63). Long time (> 5 years) since last eye examination was an independent risk factor for correctable visual impairment, OR 2.7, 95% CI [1.0, 7.3], p = 0.046. Subjects with correctable visual impairment had either low refractive error or hyperopia (spherical equivalent refraction (SER) > -0.50 D), but there was no statistically significant association between refractive error and correctable visual impairment. Regular eye examination and correction of low refractive error and hyperopia can prevent unnecessary visual impairment in the elderly.